Skeletal Muscle Strength and Endurance are Maintained during Moderate Dehydration - Périard, J. D.; Tammam, A. H.; Thompson, M. W. (International Journal of Sports Medicine, 2012)
This study investigated the effects of moderate dehydration (~2.5% body weight) on muscle strength and endurance using percutaneous electrical stimulation to quantify central and peripheral fatigue, and isolate the combined effects of exercise-heat stress and dehydration, vs. the effect of dehydration alone. Force production and voluntary activation were calculated in 10 males during 1 brief and 15 repeated maximal voluntary isometric contractions performed prior to (control) walking in the heat (35°C), immediately following exercise, and the next morning (dehydration). The protocol was also performed in a euhydrated state. During the brief contractions, force production and voluntary activation were maintained in all trials. In contrast, force production decreased throughout the repeated contractions, regardless of hydration status (P<0.001). The decline in force was greater immediately following exercise-heat stress dehydration compared with control and euhydration (P<0.001). When dehydration was isolated from acute post-exercise dehydration, force production was maintained similarly to control and euhydration. Despite the progressive decline in force production and the increased fatigability observed during the repeated contractions, voluntary activation remained elevated throughout each muscle function test. Therefore, moderate dehydration, isolated from acute exercise-heat stress, does not appear to influence strength during a single contraction or enhance fatigability.
Keywords: fatigue; neuromuscular function; force production; voluntary activation